The Relationship Between Feeding Patterns and Maternal Knowledge about Nutrition with the Incidence of Stunting in Children Age 0-5 Years in the Working Area of the Gedongan Health Center, Mojokerto City - Putri, Nadya Aisyah Sasqia; Adiwinoto, Ronald Pratama; Arundani, Prima; Nugraheni, Pramita Anindya; Adnyana, I Made Dwi Mertha (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2024)
Stunting is a prolonged state of chronic malnutrition. This disorder is characterized by having a body length-for-age or body height-for-age measurement that falls below the -2 standard deviation established by the World Health Organization (WHO). The etiology of stunting is multifaceted, encompassing factors such as nutrition, feeding practices, infectious illnesses, and household income. Maternal understanding of nutrition, including dietary factors, is also associated with the occurrence of stunting. This study aimed to establish the relationship between feeding habits and maternal knowledge of nutrition with the prevalence of stunting in the operational region of the Gedongan Health Center, located in Mojokerto City. This study is an observational analytical study employing a cross-sectional design. The study’s population consisted of all women with children residing in the working area of the Gedongan Health Center. This study encompassed 144 participants who completed the Child Feeding Questionnaire (CFQ) regarding eating practices and a questionnaire assessing maternal knowledge of nutrition. The objective was to examine the relationship between these factors to height and age. The chi-square test results indicate a statistically significant association between feeding practices and stunting (p = 0.0001) and maternal knowledge about nutrition and stunting (p = 0.0001). The survey revealed that most children had been provided with appropriate feeding patterns, and most moms had a commendable nutritional understanding. The study’s findings indicate a noteworthy relationship between feeding behaviors and mothers’ nutrition knowledge.